Comparative evaluation of some climate references of Novolazarevskaya station and Novolazarevskaya airfield - E. I. Alexandrov; A. N. Prakhov; Е. И. Александров; А. Н. Прахов (Arctic and Antarctic Research, 2017)
The results of a comparative analysis of the monthly mean of average, maximum and minimum values of air temperature, air humidity and wind speed calculated by daily data with one minute increment for the period from November 2006 to February 2012 during the months of operation of the meteorological station at the Novolazarevskaya airfield and directly at Novolazarevskaya station are given. The climatic parameters at two points of observation give high correlation index. The estimations of the trends in time series of climatic references at Novolazarevskaya station for the period 1961–2015 are also given. Приводятся результаты сравнительного анализа среднемесячных величин средних, максимальных и минимальных значений температуры воздуха, влажности воздуха и скорости ветра, рассчитанных по ежедневным данным с минутной дискретностью за период с ноября 2006 г. по февраль 2012 г. в месяцы работы метеостанции на аэродроме станции Новолазаревская и непосредственно на станции Новолазаревская. Наблюдается высокая корреляция между этими климатическими характеристиками в двух точках наблюдений. Приведены оценки тенденций временных рядов климатических характеристик на станции Новолазаревская за период 1961–2015 гг.